Autocrine inhibition of the c-fms proto-oncogene reduces breast cancer bone metastasis assessed with in vivo dual-modality imaging. (April 2014) - Jeffery, Justin J; Lux, Katie; Vogel, John S; Herrera, Wynetta D; Greco, Stephen; Woo, Ho-Hyung; AbuShahin, Nisreen; Pagel, Mark D; Chambers, Setsuko K
Breast cancer cells preferentially home to the bone microenvironment, which provides a unique niche with a network of multiple bidirectional communications between host and tumor, promoting survival and growth of bone metastases. In the bone microenvironment, the c-fms proto-oncogene that encodes for the CSF-1 receptor, along with CSF-1, serves as one critical cytokine/receptor pair, functioning in paracrine and autocrine fashion. Previous studies concentrated on the effect of inhibition of host (mouse) c-fms on bone metastasis, with resulting decrease in osteolysis and bone metastases as a paracrine effect. In this report, we assessed the role of c-fms inhibition within the tumor cells (autocrine effect) in the early establishment of breast cancer cells in bone and the effects of this early c-fms inhibition on subsequent bone metastases and destruction. This study exploited a multidisciplinary approach by employing two non-invasive, in vivo imaging methods to assess the progression of bone metastases and bone destruction, in addition to ex vivo analyses using RT-PCR and histopathology. Using a mouse model of bone homing human breast cancer cells, we showed that an early one-time application of anti-human c-fms antibody delayed growth of bone metastases and bone destruction for at least 31 days as quantitatively measured by bioluminescence imaging and computed tomography, compared to controls. Thus, neutralizing human c-fms in the breast cancer cell alone decreases extent of subsequent bone metastasis formation and osteolysis. Furthermore, we are the first to show that anti-c-fms antibodies can impact early establishment of breast cancer cells in bone.